Phytochemistry and Bioactivity of Nepeta racemosa Lam. - Fariba Heshmati Afshar; Abbas Delazar; Yahya Rahimpour; Niloufar Moharrer Navaei; Solmaz Asnaashari; Parina Asgharian* (Iranian Society of Pharmacognosy, 2021)
Background and objectives: The genus Nepeta is used in traditional medicine for the antiseptic and astringent properties in cutaneous eruptions and snake bites. Nepeta racemosa was investigated here due to the rich source of phytochemical compounds in the Nepeta genus and the lack of any phytochemical studies. Methods: The aerial parts were extracted successively using n-hexane, chloroform, and methanol (MeOH) by maceration method, respectively. The MeOH extract was exposed to C18 Sep-Pak fractionation by a step gradient of MeOH-H2O. Further purification of the fractions by preparative reversed-phase HPLC yielded three compounds. The chemical ingredients of essential oil were determined by GC-MS. Free-radical scavenging activity of the extracts, fractions, as well as their total flavonoid and phenolics contents, were assessed using the DPPH method, AlCl3, and Folin-Ciocalteu reagents, respectively. Results: Phytochemical study of 20% and 40% solid phase extraction fractions of MeOH extract yielded one iridoid (8,9-epi-7-deoxy-loganic acid) and two phenylethanoids (forsythoside B and verbascoside), correspondingly. The 4aα,7α,7aα-nepetalactone (31.70 %), germacrene D (7.39 %), n-hexadecanoic acid (6.47 %), were the main compounds of essentials oil. The MeOH extract demonstrated high activity in terms of antioxidant activity, total phenolics content along with total flavonoids content (0.09 ± 0.01 mg/mL, 1581.80 ± 10.28 mg/100g and 33.01 ± 0.02 mg/100g) as well as 40% SPE fraction (0.01 ± 0.00 mg/mL, 659.20 ± 40.32 mg/100g and 22.5 ± 0.37 mg/100g), respectively.  Conclusion: The presence of phenylethanoid derivatives as phenolic compounds appears to be an important antioxidant compound in Nepeta racemosa.